Analysis of Means-End Structures Emerging from Abbreviated Hard Laddering Interviews - Sagan, Adam; Kąciak, Eugeniusz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The paper presents a new method of evaluating the quality of ladders obtained with the abbreviated hard laddering procedure (Kąciak and Cullen 2006). It is based on an analysis of summary ladder matrix (SLM) and top of mind awareness indices (TMA), which allows one to consider not only the sequence in which consecutive ladders are produced by the respondent but also the salience of these ladders. The quality of ladders is further examined through non-symmetrical correspondence analysis of the SLM. This makes it possible to obtain additional information on the dominant dimensions in the means-end structure and also to determine which prominent ladders contribute most to the system's inertia.